Stagecoach : a western story - Brand, Max, 1892-1944 (Five Star, a part of Gale, Cengage Learning, 2013)
Sammy Greeg is a tenderfoot from New York City on the frontier to make his fortune. He has a fearless determination to succeed no matter the cost, and that makes Sammy a formidable adversary to horse thieves, robbers, and killers. When the lead starts flying, it turns out Sammy has a lot more grit than folks thought.